Equivalent lateral force and modal analysis procedures of the 2000 NEHRP provisions for buildings with damping systems - Whittaker, Andrew S.; Constantinou, Michael C.; Ramirez, Oscar M.; Johnson, Martin W.; Chrysostomou, Christis (My University, 2003)
Equivalent lateral force and modal analysis procedures for yielding buildings with damping systems were developed, validated, and incorporated in the 2000 NEHRP Provisions. The technical basis for each procedure is described in the paper together with the simplifications adopted for inclusion in the Provisions. Procedures for calculating the effective damping and effective period and higher mode damping ratios for buildings equipped with yielding, viscoelastic, linear viscous, and nonlinear viscous damping devices are presented.
Keywords: Earthquakes; Seismology; Structural design--Abstracts--Periodicals